2004
DOI: 10.2337/diacare.27.10.2478
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease, Asthma, and Risk of Type 2 Diabetes in Women

Abstract: OBJECTIVE -Inflammation plays a key role in chronic obstructive pulmonary disease (COPD) and asthma. Increasing evidence points toward a role of inflammation in the pathogenesis of type 2 diabetes. We wanted to determine the relation of COPD and asthma with the development of type 2 diabetes. RESEARCH DESIGN AND METHODS -TheNurses' Health Study is a prospective cohort study. From 1988From -1996,614 female nurses were asked biennially about a physician diagnosis of emphysema, chronic bronchitis, asthma, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
159
2
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(174 citation statements)
references
References 47 publications
(27 reference statements)
8
159
2
5
Order By: Relevance
“…The degree of excess diabetes appears to be a lesser extent than other cardiovascular risk contributing conditions. This finding has been corroborated by another large epidemiological study which showed a relative risk of incident diabetes of 1.8 in female COPD patients, following adjustment for confounders [60]. Feary and colleagues showed that this may not hold true for older COPD patients who appeared to have a slightly reduced odds ratio of having diabetes in a cross sectional ana lysis [17].…”
Section: Type II Diabetes Mellitussupporting
confidence: 64%
“…The degree of excess diabetes appears to be a lesser extent than other cardiovascular risk contributing conditions. This finding has been corroborated by another large epidemiological study which showed a relative risk of incident diabetes of 1.8 in female COPD patients, following adjustment for confounders [60]. Feary and colleagues showed that this may not hold true for older COPD patients who appeared to have a slightly reduced odds ratio of having diabetes in a cross sectional ana lysis [17].…”
Section: Type II Diabetes Mellitussupporting
confidence: 64%
“…Large population studies show that there is an increased prevalence of diabetes among COPD patients (relative risk 1.5-1.8), even in patients with mild disease [1,150]. The reasons for this association are not yet understood.…”
Section: Diabetesmentioning
confidence: 99%
“…However, there are several other diseases potentially linked to respiratory disease or its treatment with a weaker association, i.e. osteoporosis [8], cataracts [9], hypertension [10] and diabetes mellitus [11].…”
mentioning
confidence: 99%